2006
DOI: 10.1016/j.febslet.2006.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis‐inducing factor (AIF) inhibits protein synthesis by interacting with the eukaryotic translation initiation factor 3 subunit p44 (eIF3g)

Abstract: Apoptosis-inducing factor (AIF) is a ubiquitous FADbinding flavoprotein comprised of 613 amino acids and plays an important role in caspase-independent apoptosis. During apoptotic induction, AIF is translocated from the mitochondrial intermembrane space to the nucleus, where it interacts with DNA and activates a nuclear endonuclease. By performing a yeast two-hybrid screen with mature AIF, we have isolated the eukaryotic translation initiation factor 3 subunit p44 (eIF3g). Our deletion mutant analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Furthermore, our results do not exclude a role for non-nuclear proapoptotic effects of DmAIF. Indeed, mammalian AIF can exert part of its biochemical effects by arresting protein translation, through a direct interaction with eIF3g, 37 and the C. elegans AIF ortholog WAH-1 can enhance phosphatidylserine exposure of dying cells through a direct interaction with a phospholipids scramblase. 38 This means that, in different species, AIF does mediate major non-nuclear alterations in cellular physiology (protein synthesis arrest and loss of plasma membrane asymmetry) that are considered to be hallmarks of the apoptotic process, and it remains to be seen whether these changes are also influenced by DmAIF.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our results do not exclude a role for non-nuclear proapoptotic effects of DmAIF. Indeed, mammalian AIF can exert part of its biochemical effects by arresting protein translation, through a direct interaction with eIF3g, 37 and the C. elegans AIF ortholog WAH-1 can enhance phosphatidylserine exposure of dying cells through a direct interaction with a phospholipids scramblase. 38 This means that, in different species, AIF does mediate major non-nuclear alterations in cellular physiology (protein synthesis arrest and loss of plasma membrane asymmetry) that are considered to be hallmarks of the apoptotic process, and it remains to be seen whether these changes are also influenced by DmAIF.…”
Section: Resultsmentioning
confidence: 99%
“…A plausible hypothesis is that Scythe could protect AIF from degradation and perhaps favor its apoptotic action in the cytosol. Indeed, whereas the function of AIF in the nucleus is well documented (13), its action in the cytoplasm has recently emerged where it has been shown to activate caspase 7 (28). Scythe, by stabilizing and maintaining AIF in the cytosol may function as a central regulator of the action of AIF.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cereviseae, it has been demonstrated that CypA is also essential for AIF-proapoptotic activity (13). In this eukaryote, Kim et al (27) have discovered an interaction between the N-terminus of eIF3g and the AIF C-terminal region. Through this link, AIF could regulate protein synthesis during ''programmed'' cell death (PCD).…”
Section: Aif Across the Speciesmentioning
confidence: 99%